STRATEGI PEMASARAN PINGGIR JALAN PIZZA HUT SEBAGAI UPAYA BERTAHAN DARI DAMPAK PANDEMI COVID-19 DI INDONESIA - Aprilianto Amir (STIA Bengkulu, 2023)
The COVID-19 pandemic has yet shown symptoms to cease. The impact of this global plague affects wide range aspects of human life and the order of many countries in the world. Various businesses and industries have to struggle hard to endure the negative effects of the pandemic. Restaurant is one of the industries that has been hit hard by the pandemic among the important industries supporting the economy. As one of well-known players in food and beverages, Pizza Hut Indonesia also suffer the same fate. In dealing with this situation, the company made a bold effort for the sake of the company's survival by launching roadside marketing strategy along with more affordable innovative products. This paper will discuss how the strategy taken by Pizza Hut can help reduce the negative impact of the pandemic to one of the most popular multi-national franchise restaurants in Indonesia.